2020
DOI: 10.33963/kp.15163
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-induced cardiotoxicity prevention with angiotensin-converting enzyme inhibitor ramipril in women with low-risk breast cancer: results of a prospective randomized study

Abstract: and chronic forms of anthracycline-induced cardiotoxicity (AIC), which is classified into early-onset (first year) and late-onset cardiotoxicity. 6 Chronic AIC typically presents as irreversible myocardial dysfunction and heart failure (HF). The estimated incidence of HF ranges from 6.6% to 26%. 7,8 An asymptomatic INTRODUCTION Breast cancer (BC) is the most common malignancy in women worldwide. 1,2 The use of potentially cardiotoxic anthracyclines, cytostatic agents introduced many years ago, still remains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 3 publications
0
26
0
2
Order By: Relevance
“…In addition, N-terminal pro-brain natriuretic peptide and troponin are known to be relatively sensitive indicators of cardiac injury [14,23]. Some studies have used them to assist imaging methods to assess cardiotoxicity [6,14]. Of inter- est, Rigaud et al [24] and Gioffre et al [25] found that specific circulating miRNA may be a specific marker of anthracycline-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, N-terminal pro-brain natriuretic peptide and troponin are known to be relatively sensitive indicators of cardiac injury [14,23]. Some studies have used them to assist imaging methods to assess cardiotoxicity [6,14]. Of inter- est, Rigaud et al [24] and Gioffre et al [25] found that specific circulating miRNA may be a specific marker of anthracycline-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The bias assessment of involving RCTs is presented in Figure 2. There were 3 studies [4][5][6] described the method of random sequence generation clearly, of which 2 studies [5,6] also described allocation concealment. Three studies [4,5,7] described a rigorous blinding method for participants, while 4 RCTs [4,5,7,8] used standard blinding method to assess the outcomes of studies.…”
Section: Quality Evaluationmentioning
confidence: 99%
“…Treatment with dexrazoxane, β-blocker, statin or angiotensin antagonists may play a role in reducing cardiotoxicity [26]. A recent publication shows that ramipril treatment exerts potentially protective effects on cardiotoxicity [27].…”
Section: Discussionmentioning
confidence: 99%
“…B-type natriuretic peptides and N-terminal fragment of the prohormone brain natriuretic peptide are also considered routine biomarkers for cardiac dysfunction and HF diagnosis during chemotherapy. [44][45][46] The main disadvantage of these biomarkers is that they cannot be used as an early indicator of cardiotoxicity because their expressions occur after the irreversible cardiac damage. So there is an urgent need to identify new potential early detection biomarkers to provide early warning for chemotherapy-induced cardiotoxicity.…”
Section: Epigenetics and Aicmentioning
confidence: 99%
“…Several clinical studies reported that some cardiac biomarkers, such as troponin I and troponin T, could be used to confirm cardiotoxicity, and high levels of troponin indicate there is irreversible myocardial cell injury in patients with cancer who received chemotherapy. B‐type natriuretic peptides and N‐terminal fragment of the prohormone brain natriuretic peptide are also considered routine biomarkers for cardiac dysfunction and HF diagnosis during chemotherapy 44–46 . The main disadvantage of these biomarkers is that they cannot be used as an early indicator of cardiotoxicity because their expressions occur after the irreversible cardiac damage.…”
Section: Epigenetics and Aicmentioning
confidence: 99%